Pengembangan Modul IPA Terpadu Problem-Based Learning (PBL) Dengan Tema Energi Sebagai Sumber Kehidupan SMP/MTs - Novyatun Latifah; Indica Yona Okyranida; Asep Setiadi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
The purpose of the research is to design and develop an Integrated Science Module based on Problem-Based Learning (PBL), in addition, in addition, researchers also want to know the results of the student response to the trial of this Integrated Science Module product for junior high school students (junior high school) and equivalent. The research method used in this study is research and develompent method with ADDIE development model. The population is students of SMP Muhamadiyah Pabuaran, with suchrt scale research techniques. The instruments used are validation tests and student response tests in the form of questionnaires. Data analysis techniques use descriptive analysis techniques that calculate the percentage of validation values. The results of the study obtained an average score of 75% for media experts with the categories "good" and "decent", an average score of 83.3% for material experts and an average of 80.86% for language experts from the results containing that the development of a Problem Based Learning Based Integrated IPA module (PBL) with the Theme of Energy as a Source of Life SMP /MTS got the category " very feasible" tested in schools. In addition, the results of the student response test got 90.67% results with the category "very feasible" used as a learning medium in the school. The results of this study are useful to improve the quality of learning modules at junior high school/ mts level.